Structuring light to control photon entanglement - Lovemore, Michael Andrew Charles (University of the Witwatersrand, Johannesburg, 2022)
Photon entanglement, either spatially, temporally, or even in terms of its polarization, has become an increasingly important field of interest in the world of quantum mechanics. The importance becomes apparent when looking at quantum protocols such as quantum teleportation, commu nication, and quantum information. These entangled photons are often generated through a well known non-linear process known as spontaneous parametric down-conversion (SPDC), where a high-energy pump beam impinges on a non-linear crystal and generates two lower energy down converted entangled photons. The intensity and phase profile of the pump beam influences the dimension of entanglement that exists between the two generated photons. This pump beam shape can be altered through the use of optical devices such as spatial light modulators (SLMs) in order to achieve desired entanglement spectra. This dissertation serves as an introduction to structured light and photonics with an emphasis on the spatial modes of light and the inter section of quantum mechanics with optics. A description concerning the tailoring of the field of light with spatial light modulators is presented. These SLMs are also useful when measur ing some properties related to entangled photons. Some of the quantum measurements that are discussed here include the spiral bandwidth, Bell measurements, and quantum state tomography measurements. Lastly, some novel work is presented, where we demonstrate a basis-independent approach to shaping the pump beam, in order to achieve a desired entanglement spectrum.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, School of Physics, University of the Witwatersrand, Johannesburg, 2022
Keywords: Quantum mechanics; Spatial modes of light; Schrödinger equation; Reduced Density Matrix; Measures of entanglement; Spatial Light Modulators (SLMs); UCTD; SDG-9: Industry, innovation and infrastructure; SDG-4: Quality education